Jean Vigo - L'intégrale - Vigo, Jean; Kaufman, Boris (Gaumont Vidéo, 2018)
Even among cinema's greatest legends, Jean Vigo stands alone. The son of a notorious anarchist, Vigo had a brief but brilliant career making poetic, lightly surrealist films before his life was cut tragically short by tuberculosis at age twenty-nine. Like the daring early works of his contemporaries Jean Cocteau and Luis Buñuel, Vigo's films refused to play by the rules. This set includes all of Vigo's titles: "À propos de Nice", an absurdist, rhythmic slice of life from the bustling coastal city of the title; "Taris", an inventive short portrait of a swimming champion; "Zéro de conduite", a radical, delightful tale of boarding-school rebellion that has influenced countless filmmakers; and, of course, "L'Atalante", widely regarded as one of cinema's finest achievements, about newlyweds beginning their life together on a canal barge. These are the endlessly witty, visually adventurous works of a pivotal film artist. [www.amazon.com]
Keywords: Blu-Ray-Disc